Effect of air-blowing duration on the bond strength of current one-step adhesives to dentin. Issue 8 (August 2017) - Fu, Jiale; Saikaew, Pipop; Kawano, Shimpei; Carvalho, Ricardo M.; Hannig, Matthias; Sano, Hidehiko; Selimovic, Denis
Abstract: Objectives: To evaluate the influence of different air-blowing durations on the micro-tensile bond strength (μTBS) of five current one-step adhesive systems to dentin. Methods: One hundred and five caries-free human molars and five current one-step adhesive systems were used: ABU (All Bond Universal, Bisco, Inc.), CUB (CLEARFIL™ Universal Bond, Kuraray), GPB (G-Premio BOND, GC), OBA (OptiBond All-in-one, Kerr) and SBU (Scotchbond Universal, 3M ESPE). The adhesives were applied to 600 SiC paper-flat dentin surfaces according to each manufacturer's instructions and were air-dried with standard, oil-free air pressure of 0.25 MPa for either 0 s, 5 s, 15 s or 30 s before light-curing. Bond strength to dentin was determined by using μTBS test after 24 h of water storage. The fracture pattern on the dentin surface was analyzed by SEM. The resin–dentin interface of untested specimens was visualized by panoramic SEM image. Data from μTBS were analyzed using two-way ANOVA (adhesive vs. air-blowing time), and Games-Howell (a = 0.05). Results: Two-way ANOVA revealed a significant effect of materials (p = 0.000) and air-blowing time (p = 0.000) on bond strength to dentin. The interaction between factors was also significantly different (p = 0.000). Maximum bond strength for each system were recorded, OBA/15 s (76.34 ± 19.15 MPa), SBU/15 s (75.18 ± 12.83 MPa), CUB/15 s (68.23 ± 16.36 MPa), GPB/30 s (55.82 ± 12.99 MPa) and ABU/15 s (44.75 ± 8.95 MPa). The maximum bond strength of OBA and SUB were significantly higher than that of GPB and ABU (p < 0.05). Significance: The bond strength of the current one-step adhesive systems is material-dependent (p = 0.000), and was influenced by air-blowing duration (p = 0.000). For the current one-step adhesive systems, higher bond strengths could be achieved with prolonged air-blowing duration between 15–30 s.